The Protection of Domestic Industry through Safeguards Instrument GATT/WTO and Its Implementation on Downstream Steel Industry In Indonesia - Johan, Eva (Indonesian Journal of International Law, 2012)
World Global Crisis causes all trade world find difficulties. There will be increasing particularly import product in a country, including to Indonesian market. This getting worse by the implementation of free trade agreement between ASEAN member and China in the form of ASEAN China Free Trade Agreement (ACFTA). Steel as national strategic industry is a vital industry for developing country like Indonesia, so government should protect it against incursion of import products. Indonesia as member of WTO can use GATT/WTO safeguards instrument to protect domestic downstream steel industry from increasing import of downstream steel product. The protection for domestic industry through safeguards GATT/WTO instrument in Indonesia executed under trade security instruments, namely President Decision (Kepres No. 84 Year 2002) and Act 17/2006 (UU No. 17 Year 2006). Therefore, this article analyzes: first, how to protect domestic industry through safeguards GATT/WTO instrument in Indonesia and, how does implementation of safeguards instrument has protecting Indonesia domestic downstream steel industries.